The impact of high-intensity interval training on cerebrovascular function in the APP/PS1 mice - Zhu, Lei; Cai, Ming; Lu, Zhe; Wang, Qi; Zhai, Teng; Hu, Jingyun (Frontiers in Aging, 2025)
AbstractAlzheimer’s disease (AD), the most commonly diagnosed form of senile dementia worldwide, is closely associated with aging and distinct neuropathological features. Recent studies highlight that up to 90% of individuals, either preclinical or clinical, diagnosed with vascular pathology in the context of AD exhibit thickening and hyalinization of the media in small and medium-sized cerebral vessels. Exercise has emerged as a potential, non-pharmaceutical, and cost-effective intervention for the prevention and treatment of AD. However, there is limited research exploring the effects of high-intensity interval training (HIIT) on cerebrovascular function in AD.MethodsFour-month-old female C57BL/6 J mice and APP/PS1 transgenic mice were initially acclimated to a standard diet for 1 week. The two groups were then divided into sedentary and exercise cohorts, with the exercise group engaging in a 6-week HIIT regimen. Post-intervention, hippocampal specimens were collected for analysis. Aβ and Tau protein levels were measured to assess AD pathology, while cognitive function was evaluated using the eight-arm radial maze and BDNF mRNA expression. Additionally, markers of cerebrovascular function-including VEGF, EPO, eNOS, GPR68, and ET-1-were examined, and HIF-1α was utilized to assess the hippocampal response to AD pathology.ResultsHIIT significantly reduced reference memory errors (p = 0.025) and markedly upregulated Bdnf mRNA expression (p < 0.001) specifically in APP/PS1 mice. Furthermore, HIIT significantly decreased protein levels of AD pathological markers p-TAU (p = 0.001) and APP (p = 0.002) in APP/PS1 mice. HIIT significantly increased the mRNA (p < 0.001) and protein (p = 0.003) levels of EPO and Vegfa mRNA (p < 0.001) levels to stimulate pro-angiogenic signal in APP/PS1 mice. HIIT also significantly increased both the mRNA and proteins levels of eNOS expression (p < 0.001) while decreasing the mRNA and proteins levels of ET-1 (p < 0.001) and GPR68 (p < 0.001) to enhance vasodilation in APP/PS1 mice. Finally, HIIT significantly increased HIF-1α expression at both protein and mRNA levels (p < 0.001), independent of genotype.ConclusionHIIT ameliorates cognitive function and reduces hallmark AD pathology. This positive effect is potentially mediated through cerebral microangiogenesis, cerebrovascular function regulation, and hypoxic metabolism. HIIT represents a promising non-pharmacological strategy for targeting multiple aspects of AD pathophysiology.